Molecular Analysis of Putative Fibrobacter Succinogenes Xylanase Genes Subcloned from Recombinant Xylanolytic Plasmid pBX6 - Hassan, Nurhasmimi (2006)
pBX6 is a recombinant plasmid containing a 3 kb fragment of insert DNA from Fibrobacter succinogenes S85 genomic DNA which encodes a xylanase gene. An E.coli HB101 colony cell, carrying pBX6 expresses xylanase activity which can be detected on Remazol Brilliant Blue-Xylan (RBB-Xylan) agar plates supplemented with Ampicillin as a clear halo zone against a dark blue background. This characteristic allows xylanase gene to be used as a selectable chromogenic marker on any vector system. The insert DNA from Fibrobacter succinogenes S85 in the plasmid pBX6 encodes two putative xylanase regions which are named ORF 1 and ORF 2. These two ORF were amplified by the polymerase chain reaction (PCR). A pair of PCR primers for the detection of two ORF from plasmid pBX6 has been synthesized and has revealed the putative xylanase gene of approximately 1,224 bp for ORF 1 and 1,450 bp for ORF 2. Both ORF was separately subcloned into E.coli JM109 by using pGEM T-Easy vector. Recombinant plasmid DNA from a positive clone for both ORF was designated as pGEM-X1 and pGEM-X2. The insertion of the ORF 1 and ORF 2 was confirmed using restriction enzyme analysis and PCR amplification. The nucleotide sequence determined showed high similarity to the original gene and also high homology with other bacterial xylanases such as Pseudomonas fluorescence and Butyrivibrio fibrisolvens. The homology ranged from 57% to 94% for clone pGEM-X1 while for clone pGEM-X2, the homology ranged from 88% to 92% with xylanase from F. succinogenes S85 (xynC-xyl). Xylanase activity assay was done to further confirm its presence in the recombinant plasmid pGEM-X1 and pGEM-X2. However, the results showed there was no activity for both subclone using the Somogyi-Nelson assay for reducing sugar. Based on the results obtained, recombinant plasmids pGEM-X1 and pGEM-X2 were successfully inserted into pGEM-T Easy vector and introduced into E.coli JM109.